Cancer cost profiles: The Epicost estimation approach - Francisci, Silvia; Capodaglio, Guilia; Gigli, Anna; Mollica, Cristina; Guzzinati, Stefano (Frontiers in Public Health, 2022)
Sustainability of cancer burden is becoming increasingly central in the policy makers’ debate, and poses a challenge for the welfare systems, due to trends toward greater intensity of healthcare service use, which imply increasing costs of cancer care. Measuring and projecting the economic burden associated with cancer and identifying effective policies for minimizing its impact are important issues for healthcare systems. Scope of this paper is to illustrate a novel comprehensive approach (called Epicost) to the estimation of the economic burden of cancer, based on micro-data collected from multiple data sources. It consists of a model of cost analysis to estimate the amount of reimbursement payed by the National Health Service to health service providers (hospitals, ambulatories, pharmacies) for the expenses incurred in the diagnoses and treatments of a cohort of cancer patients; these cancer costs are estimated in various phases of the disease reflecting patients’ patterns of care: initial, monitoring and final phase. The main methodological features are illustrated using a cohort of colon cancer cases from a Cancer Registry in Italy. This approach has been successfully implemented in Italy and it has been adapted to other European countries, such as Belgium, Norway and Poland in the framework of the Innovative Partnership for Action Against Cancer (iPAAC) Joint Action, sponsored by the European Commission. It is replicable in countries/regions where population-based cancer registry data is available and linkable at individual level with administrative data on costs of care.